Treatment of 5th metacarpal neck fractures with titanium elastic nail using local anesthesia and hematoma block (Annals of Medical Research, 2024)
Aim: Surgical treatment of 5th metacarp neck fractures using titanium elastic nail (TEN) is performed under general anesthesia or axillary block. In this study, our aim is to present the clinical and radiological results of patients who underwent surgery under local anesthesia for the TEN entry site and hematoma block for fracture reduction.Materials and Methods: There were 14 patients who had 5th metacarpal neck fractures treated with intramedullary TEN (titanium elastic nail) and met the inclusion criteria were evaluated retrospectively. Radiologically, metacarpal shortness and volar angulation angles at the time of admission, after reduction in the ER and after surgical intervention when the fusion had been achieved were evaluated. Clinically, rotational deformity, range of motion of the affected finger were evaluated according to Quick DASH scores.Results: The patients, all male, were aged between 18 and 46 ( mean 26) years and had injuries on the dominant side. The volar angulation after surgical intervention a mean of 17.2° (10-22°) was achived at the final follow-up. The metecarpal shortness was determined to be mean 4.4 mm (1.8-7.3mm) on first presentation, 3 mm (2-5 mm) after reduction in ER, and 2 mm (1.2-3.3mm) at the final follow-up examination in surgically treated group compared to healthy side. Radiological bone union was observed in mean 35 days.  Finger flexion and extension were determined to be full at the end of the 3rd month and no rotational deformity was observed. The mean Quick DASH score of the patients was 1.5 (1.2-2).Conclusion: 5th metacarpal fractures with TEN under hematoma blockage and local anesthesia and leaving the proximal end out of the skin is a safe method for the treatment of such fractures.
Keywords: Metecarpal fractures; IM fixation; Local anesthesia